Hematogenous tuberculosis in the puerperal gravid state obstetrical control and tisiológico in fifteen cases - Migone, Oscar (2015)
Hematogenous tuberculosis occurs at higher rates in pregnant than in non-pregnant women; 10% of TB cases in the first and 5% by the latter. This study was conducted in two groups of patients 150 and 200 respectively, under similar conditions for both. Have controlled 15 patients with bloodborne forms of pulmonary tuberculosis, in a systematic and ongoing, during and after grávidopuerperal state for a period of at least four years in total, with a treatment that I implied: permanent hospitalization and hygienic-dietary regimen -medicamentoso right. It has been observed in these patients obstetric pathology similar to that of very advanced tuberculosis not hematógenas: premature termination of pregnancy, anemia true; hipodinomias in labor; subinvolution uterine postpartum; etc., at higher percentages than usual. But they have not noticed genital bleeding in any case, made striking by the fact of being frequent in the delivery of non-hematogenous tuberculosis. Other obstetric characteristics not dosed their small numbers or large variation.